Individual Differences in Deductive Reasoning: A Narrative Review - Crivello, María del Carmen; Macbeth, Guillermo; Fioramonti, Mauro; Razumiejczyk, Eugenia (Pensando Psicología, 2016)
Introduction: This study addresses the issue of individual differences in deductive reasoning. It covers some of the variables related to the field: cognitive skills, development, gender and culture of people.Objective: To provide a narrative review of the main proposals in the area, emphasizing social factors.Methodology: A qualitative analysis of existing literature is performed, assessing mainly classic and some recent contributions.Results: Variables of individual differences that can contribute to a better understanding of the phenomenon under study have been detected.Conclusion: The main findings and limitations of the work, related to the combination of evidence in future meta-analytic studies, were summarized.
Keywords: development; individual differences; gender and culture; intelligence; reasoning